Methylenetetrahydrofolate Reductase Enzyme Mutations and Relationship of Homocysteine Vitamin B12 and Folate Blood Levels - Günebak Şahin, Tuba; Sayal, Berkan; Coşgun, Erdal; Besler, Tanju; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: The purpose of this study is to investigate the influence of MTHFR gene polymorphisms which may effect the interaction in between homocysteine, folic acid and vitamin B12 metabolisms. STUDY DESIGN: The subject of this study is consisted of 165 patients who were obtained from “Hacettepe University Maternal Fetal Medicine Data Base”. These were married women of childbearing age with MTHFR gene polymorphisms who experienced bad obstetrical history. Plasma total homocysteine, serum folic acid and vitamin B12 levels of the subjects were analysed and the interrelation between these nutritional factors was examined. RESULTS: Both folic acid and vitamin B12 are significantly important and effective factors in homocysteine metabolism in MTHFR mutant subjects. CONCLUSION: Folic acid is a much more important mass measure for controlling elevation of plasma homocysteine concentration.